Financial Development : Structure and Dynamics - de la Torre, Augusto; Feyen, Erik; Ize, Alain (2012)
This paper analyzes the bright and dark sides of the financial development process through the lenses of the four fundamental frictions to which agents are exposed -- information asymmetry, enforcement, collective action, and collective cognition. Financial development is shaped by the efforts of market participants to grind down or circumvent these frictions, a process further spurred by financial innovation and scale and network effects. The analysis leads to broad predictions regarding the sequencing and convexity of the dynamic paths for a battery of financial development indicators. The method used also yields a robust way to benchmark the financial development paths followed by individual countries or regions. The paper explores the reasons for path deviations and gaps relative to the benchmark. Demand-related effects (past output growth), financial crashes, and supply-related effects (the quality of the enabling environment) all play an important role. Informational frictions are easier to overcome than contractual frictions, not least because of the transferability of financial innovation across borders.